Tourism Product Innovation Strategy At Kokokan Tourism Attraction, Petulu Village, Ubud District - Made Satria Budi Kusuma; Ni Putu Ratna Sari; I Putu Sudana, I Putu Sudana (International journal of technology and education research, 2025)
The Kokokan Tourist Attraction in Petulu Village, Ubud, has a unique characteristic as the habitat of Kokokan (white herons) that live in colonies. However, their presence is still seasonal, making tourism product innovation essential to maintain tourist interest throughout the year. This study aims to identify the existing condition of the Kokokan tourist attraction, analyze its internal and external factors, and formulate appropriate tourism product innovation strategies to enhance the destination's competitiveness. This research applies a descriptive qualitative and quantitative (mixed methods) approach, with data collected through observation, in-depth interviews, questionnaires, and documentation. The sample consisted of 100 respondents, including tourists, local communities, attraction managers, and other stakeholders, selected using a purposive sampling technique. Data were analyzed using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and the Internal–External (IE) Matrix to formulate effective tourism product innovation strategies. The results show that the Kokokan Tourist Attraction is currently at the stagnation stage within the Tourism Area Life Cycle (TALC) framework, characterized by fluctuating tourist visits and limited supporting facilities. The SWOT and IE analyses place the destination in position V (Hold and Maintain), indicating that the recommended strategy is to sustain and maintain the attraction by focusing on product development and market expansion. The proposed innovation strategies include diversifying attractions based on environmental and cultural values, utilizing digital technology for promotion, improving tourism facilities, and empowering the local community through training and active participation in tourism management.